2019
DOI: 10.9789/2175-5361.2019.v11i1.11-19
|View full text |Cite
|
Sign up to set email alerts
|

Nursing diagnoses in elderly people admitted in surgical unit / Diagnósticos de enfermagem em idosos internados em unidade cirúrgica

Abstract: Objetivo: identificar os diagnósticos de enfermagem em idosos internados em unidade cirúrgica, determinar a prevalência desses diagnósticos, verificar associação entre os diagnósticos mais prevalentes e as características definidoras/fatores de risco. Métodos: Estudo exploratório-descritivo, transversal, quantitativo, realizado com 38 idosos internados em um hospital universitário do Sul do Brasil. A coleta de dados ocorreu por meio da aplicação do histórico de enfermagem. Para análise utilizou-se a Taxonomia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Although reporting an incorrect perception about one's own health status is a highly sensitive cue to identify this diagnosis (Amaral et al, 2019;Borba et al, 2019;Martins et al, 2019;Zeleníková & Žiaková, 2012), we believe that the fact that we only showed one DC for this ND was insufficient for the other experts to value it. On the other hand, insufficient knowledge of therapeutic regimens may also have been considered a factor related to the ND ineffective health management (00078).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Although reporting an incorrect perception about one's own health status is a highly sensitive cue to identify this diagnosis (Amaral et al, 2019;Borba et al, 2019;Martins et al, 2019;Zeleníková & Žiaková, 2012), we believe that the fact that we only showed one DC for this ND was insufficient for the other experts to value it. On the other hand, insufficient knowledge of therapeutic regimens may also have been considered a factor related to the ND ineffective health management (00078).…”
Section: Discussionmentioning
confidence: 75%
“…The ND deficient knowledge (00126), which was related to a low educational level and characterized by the patient's report of not knowing how to inform his previous history of diseases and not understanding his current health status, was identified by only two experts. Although reporting an incorrect perception about one's own health status is a highly sensitive cue to identify this diagnosis (Amaral et al., 2019; Borba et al., 2019; Martins et al., 2019; Zeleníková & Žiaková, 2012), we believe that the fact that we only showed one DC for this ND was insufficient for the other experts to value it. On the other hand, insufficient knowledge of therapeutic regimens may also have been considered a factor related to the ND ineffective health management (00078).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation